Phenotypical of correlation between quantitative signs at the early varieties of pea vegetable (Pisum sativum L. partim). - В. М. Стригун (Plant Varieties Studying and Protection)
Asa result of supervisions, estimation, description, and analysis of 13 morphological, biological, biometrycal and economic valuable signs 26 varietis of pea vegetable are set sizes of phenotypical coefficients of correlation between them.